(untitled) (Perner’s Contacts, 2011)
Travelling salesman problem belongs to the elementary operational research problem. In the practical applications it can have a lot of modifications. The modifications flow from specifics of solved problem. In the presented article we deal with one of them. Concretely it deals with the problem, in which the travelling salesman movement is partially directed.